As ‘liaisons’ em francês (Polifonia, 2002)
ABSCTRACT: The aim of this paper is to analyze the process of syllabification as a result of liaison and elision in French. The case of ‘h aspiré’ is then considered an abstract segment, which inhibits the application of the vowel deletion rule.